ANALYZING THE STRUCTURE AND ROLE OF CAPITAL MARKETS IN INDIA - Dr. ARIF ARFAT (Utilitas Mathematica, 2025)
Money is a crucial component of the production process in every organization. An efficient financial system creates ample capital for investment, savings, and lending, so benefiting the economy as a whole. The ability to accumulate savings is closely correlated with the ability to generate profits, which is contingent upon the ability to save money. This system can be conceptualized as an assemblage of smaller systems that collaborate harmoniously to accomplish the intended result while adhering to the limitations you establish. In finance, the term "system" refers to an intricate network of interdependent institutions that collaborate to enhance a nation's economy.